Effects of ambient temperature and precipitation on the risk of dengue fever: A systematic review and updated meta-analysis - Li, Yanbing; Dou, Qiujun; Lu, Yuanan; Xiang, Hao; Yu, Xuejie; Liu, Suyang (Environmental research, 2020)
We systematically reviewed the published studies on the relationship between dengue fever and meteorological factors and applied a meta-analysis to explore the effects of ambient temperature and precipitation on dengue fever. We completed the literature search by the end of September 1st, 2019 using databases including Science Direct, PubMed, Web of Science, and Google Scholar. We extracted relative risks (RRs) in selected studies and converted all effect estimates to the RRs per 1 °C increase in temperature and 10 mm increase in precipitation, and combined all standardized RRs together using random-effect meta-analysis. Our results show that dengue fever was significantly associated with both temperature and precipitation. Our subgroup analyses suggested that the effect of temperature on dengue fever was most pronounced in high-income subtropical areas. The pooled RR of dengue fever associated with the maximum temperature was much lower than the overall effect. Temperature and precipitation are important risk factors for dengue fever. Future studies should focus on factors that can distort the effects of temperature and precipitation. •Both temperature and precipitation were significantly associated with risk of dengue fever.•The effect of temperature on dengue fever is greatest when exposure was on a weekly basis.•High-income countries in the subtropical region are at higher risk of dengue fever.